(3GdLed aj CUhd UfGYI GdCMcGe (B( (3GdJLhe (B)s - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3Efi LeYJ ai cJGHi gPG CUhd UfGYI GdCMcGe hLedgG hGdWQjb Edi GdJUQa ajgG s
(3BNQgG (B:s
(3hdGjbWY GdMce Ydi CeQG HOG GdGHTgGOJjf bhJjf hdG jYed HGdMce GdG HYO GdfXQ GdcKjQI hGdacQI hGdJCed GdTGai hfNJe GdebGdI GdQGHYI HgPG GdHGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1 / 1509) s
Keywords: (3Gdadcs